2019
DOI: 10.1186/s13104-019-4628-y
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of maternal near misses and the role of delays in Ethiopia: a hospital based cross-sectional study

Abstract: Objectives This study was aimed to assess the magnitude of maternal near misses and the role of delays including other risk factors. A Hospital based cross sectional study was conducted at three referral hospitals of Amhara region on 572 mothers who came to obtain obstetrics care services from February 01 to July 30, 2018. Results The magnitude of maternal near miss was 26.6% (95% CI 23, 30). With regards to delays, 83 (14.5%), 226 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
(28 reference statements)
6
12
2
Order By: Relevance
“…If a mother lacks ANC, minor obstetric conditions are not detected and managed early, serious complications and MNM will likely develop. This finding is contradictory to studies carried out in Bolivia [44] and northern Ethiopia [45], which indicated that routine ANC has an indirect impact on a maternal near-miss, likely by preventing the delay in seeking treatment through raising awareness of timely care. Therefore, the concerted effort needed by health care providers to track those mothers without antenatal care is key in reducing the incidence of MNM.…”
Section: Discussioncontrasting
confidence: 95%
“…If a mother lacks ANC, minor obstetric conditions are not detected and managed early, serious complications and MNM will likely develop. This finding is contradictory to studies carried out in Bolivia [44] and northern Ethiopia [45], which indicated that routine ANC has an indirect impact on a maternal near-miss, likely by preventing the delay in seeking treatment through raising awareness of timely care. Therefore, the concerted effort needed by health care providers to track those mothers without antenatal care is key in reducing the incidence of MNM.…”
Section: Discussioncontrasting
confidence: 95%
“…Second, maternal delay (time to reach the final care health facility) was found to have a significantly associated factor with a maternal near miss. This finding is in line with the study done in south Ethiopia, the Amhara region, the Tigray region, and Jimma [26,27,31,32] respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Women with no ANC were also more likely to develop MNM compared to women who had at least one. Similar association of no ANC and MNM has been previously reported in Ethiopia [ 36 , 37 ], Brazil [ 38 ], and Nigeria [ 39 ]. This indicates the importance of ANC in identifying pregnancy complications and providing early treatment which gives the opportunity for early detections and treatments of complications thereby reducing near miss events.…”
Section: Discussionsupporting
confidence: 87%